Public goods, public value and public audit: the Redmond review and English local government - Peter Murphy; Katarzyna Lakoma; Peter Eckersley; Bernard Kofi Dom; Martin Jones (Public Money & Management, 2022)
Following multiple critical reviews of local audit arrangements, the UK government is poised to improve public oversight of English council finances to try to identify and address risks as they emerge. This article traces the growing realization that previous audit arrangements were ineffective and suggest that the New Public Management-inspired approach of outsourcing, fragmentation and austerity increased these concerns. The authors highlight the enduring importance of public oversight of public spending in order to protect the delivery of public goods.
Keywords: 330; England; financial resilience; local government finance; public audit; public value; Redmond review